2021
DOI: 10.1021/acs.jmedchem.1c00491
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinedione “Magic Bullets” Simultaneously Targeting PPARγ and HDACs: Design, Synthesis, and Investigations of their In Vitro and In Vivo Antitumor Effects

Abstract: Monotargeting anticancer agents suffer from resistance and target nonspecificity concerns, which can be tackled with a multitargeting approach. The combined treatment with HDAC inhibitors and PPARγ agonists has displayed potential antitumor effects. Based on these observations, this work involves design and synthesis of molecules that can simultaneously target PPARγ and HDAC. Several out of 25 compounds inhibited HDAC4, and six compounds acted as dual-targeting agents. Compound 7i was the most potent, with act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 110 publications
5
29
0
Order By: Relevance
“…Most recently, Tilekar et al [97] and Upadhyaya et al [99] designed compounds 32-34 (Figure 7) with the intention of using the TZD group as ZBG. Further investigations by Tilekar et al [160] with the objective of designing dual HDAC4, HDAC8, and PPARγ inhibitors led to exemplary compound 85 and 86, which differ in the substitution pattern of the naphthyl linker compared to 32-34, forming a more extended shape. In silico analysis supported a complexation via the TZD group in HDAC4.…”
Section: Thiazolidinedione (Tzd) Warheadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Tilekar et al [97] and Upadhyaya et al [99] designed compounds 32-34 (Figure 7) with the intention of using the TZD group as ZBG. Further investigations by Tilekar et al [160] with the objective of designing dual HDAC4, HDAC8, and PPARγ inhibitors led to exemplary compound 85 and 86, which differ in the substitution pattern of the naphthyl linker compared to 32-34, forming a more extended shape. In silico analysis supported a complexation via the TZD group in HDAC4.…”
Section: Thiazolidinedione (Tzd) Warheadsmentioning
confidence: 99%
“…Evaluation of 86 showed an IC 50 of 1.1 µM toward HDAC4, yielded cell apoptosis in several cancer cell lines, and caused DNA fragmentation in CEM cells with an IC 50 value of 9.6 µM. Additional evaluation of 85 in CCRF-CEM tumor xenografts led to significant tumor regression [160]. Follow-up studies by Tilekar et al [161] identified TZD derivatives with a pyridine linker, replacing the naphthyl group.…”
Section: Thiazolidinedione (Tzd) Warheadsmentioning
confidence: 99%
“…TZD ligands act via activation of the gamma type of peroxisome proliferator-activated receptors (PPARγ) in the nucleus [16,17]. Furthermore, some TZD ligands are capable to inhibit aldose reductase (ALR2), protein tyrosine phosphatase 1B (PTP1B) and α-glucosidase [18]. Very recently, we reported on TZD-containing ligands, which are capable to inhibit HDAC4 [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some TZD ligands are capable to inhibit aldose reductase (ALR2), protein tyrosine phosphatase 1B (PTP1B) and α-glucosidase [18]. Very recently, we reported on TZD-containing ligands, which are capable to inhibit HDAC4 [18,19]. Enzyme activity assays of the HDAC family demonstrated activity of TZD ligands against HDAC4 or HDAC8 depending on the substitution pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation